Recent Development of Polyolefin‐Based Microporous Separators for Li−Ion Batteries: A Review - Heidari, Ali Akbar; Mahdavi, Hossein (Chemical record, 2020)
Secondary Li−ion batteries have been paid attention to wide‐range applications of power source for the portable electronics, electric vehicle, and electric storage reservoir. Generally, lithium‐ion batteries are comprised of four components including anode, cathode, electrolyte and separator. Although separators do not take part in the electrochemical reactions in a lithium‐ion (Li−ion) battery, they conduct the critical functions of physically separating the positive and negative electrodes to prevent electrical short circuit while permitting the free flow of lithium ions through the liquid electrolyte that fill in their open porous structure. Hence, the separator is directly related to the safety and the power performance of the battery. Among a number of separators developed thus far, polyethylene (PE) and polypropylene (PP) porous membrane separators have been the most dominant ones for commercial Li−ion batteries over the decades because of their superior properties such as cost‐efficiency, good mechanical strength and pore structure, electrochemical stability, and thermal shutdown properties. However, there are main issues for vehicular storage, such as nonpolarity, low surface energy and poor thermal stability, although the polyolefin separators have proven dependable in portable applications. Hence, in this review, we decide to provide an overview of the types of polyolefin microporous separators utilized in Li−ion batteries and the methods employed to modify their surface in detail. The remarkable results demonstrate that extraordinary properties can be exhibited by mono‐ and multilayer polyolefin separators if they are modified using suitable methods and materials. Separators physically separate the positive and negative electrodes to prevent electrical short circuit. Separators permit the free flow of lithium ions through the liquid electrolyte that fill in their open porous structure. Polyolefin porous membranes have been extensively utilized as separators because of their appreciable mechanical strength, high chemical and electrochemical stability, cost‐efficiency, high porosity and suitable thermal shutdown property